Where we stand : class matters - hooks, bell, 1952-2021 (Routledge, 2000)
Drawing on both her roots in Kentucky and her adventures with Manhattan coop boards, bell hooks provides a successful black woman's reflection, personal, straightforward, and rigorously honest on how our dilemmas of class and race are intertwined, and how we can find ways to think beyond them."--Page 4 of cover